Experimental study of metallothionein synthesis in modeling hyperthermic intraoperative intraperitoneal chemoperfusion with cysplatinum - Pykhtieieva, E. D.; Pykhtieieva, E. G.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2018)
In an experiment on white wild-type laboratory rats, it was shown that 90 minutes after intraperitoneal administration of cisplatin at a dose of 4 mg / kg as a solution heated to 43 °C, the integral level of metallothionein significantly increased in the organs. Metallothionein actively binds toxic compounds of metals, including platinum. This may be one of the main reasons for developing resistance to platinum drugs with repeated courses of chemotherapy. Fast inductive synthesis of MT with the introduction of heavy metal compounds is one of the mechanisms of adaptation of the organism to the introduction of a highly toxic platinum compound. The binding of platinum to the sulfhydryl groups of metallothionein reduces the side effect of cisplatin while simultaneously decreasing its antitumor activity. It is not recommended to use the main metallothionein inducers (Zn, Se, antioxidants) in patients with cisplatin sensitive tumors before chemotherapy courses.